2003
DOI: 10.1207/s15324796abm2601_05
|View full text |Cite
|
Sign up to set email alerts
|

Relation of cognitive appraisal to cardiovascular reactivity, affect, and task engagement

Abstract: The relation of primary cognitive appraisals to cardiovascular reactivity, affect, task engagement, and perceived stress was examined in 56 men (ages 18-29). Systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate, preejection period, stroke index, cardiac index, and total peripheral resistance were assessed at rest and during performance of a computerized mental arithmetic task. Extending on prior investigations, threat and challenge appraisals were assessed independently from one another an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
74
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 31 publications
8
74
0
Order By: Relevance
“…As illustrated in Table 2, 47% (28/60) of HPV16-negative patients were positive "responders" to E6 compared to only 14% (2/14) of HPV16-positive patients, χ 2 (1) = 4.94, p < .03. This association was also observed for E7 [44][45][46][47][48][49][50][51][52][53][54][55][56][57] and L1 382-396 peptides, both χ 2 (1)s > 5.40, ps < .03.…”
Section: T-cell Response To Hpv-16 Peptides In Relation To Participansupporting
confidence: 58%
See 1 more Smart Citation
“…As illustrated in Table 2, 47% (28/60) of HPV16-negative patients were positive "responders" to E6 compared to only 14% (2/14) of HPV16-positive patients, χ 2 (1) = 4.94, p < .03. This association was also observed for E7 [44][45][46][47][48][49][50][51][52][53][54][55][56][57] and L1 382-396 peptides, both χ 2 (1)s > 5.40, ps < .03.…”
Section: T-cell Response To Hpv-16 Peptides In Relation To Participansupporting
confidence: 58%
“…Finally, it has been argued that the assessment of life events is often not as strongly related to health outcomes as one would expect because how an individual appraises and copes with each event is likely to lead to varying outcomes (52,53). Studies have demonstrated that the cognitive appraisal of a stressor affects the subsequent physiological responses to that stressor (54), suggesting the relative importance of one's appraisal of a stressful event over the objective occurrence of that event in determining health outcomes. For example, high levels of stressful life events predicted respiratory illness, but only among those individuals who exhibited high physiological reactivity to a laboratory stressor (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is possible that emotion will prove to be relatively unimportant and that other mental processes such as motivational states or cognitive appraisals will prove to be the critical psychological mechanisms linking stress and the immune system (cf. Maier, Waldstein, & Synowski, 2003).…”
Section: Mechanisms Of Stress Effects On the Immune Systemmentioning
confidence: 99%
“…Finally, it is possible that emotion will prove to be relatively unimportant and that other mental processes such as motivational states or cognitive appraisals will prove to be the critical psychological mechanisms linking stress and the immune system (cf. Maier, Waldstein, & Synowski, 2003).In terms of biological mechanisms, the field is further along, but much remains to be learned. A series of studies in the mid-1990s was able to show via beta-adrenergic blockade that activation of the sympathetic nervous system was responsible for the immune system effects of acute stressors (Bachen et al, 1995;Benschop, Nieuwenhuis, et al, 1994).…”
mentioning
confidence: 99%
“…In contrast, a challenge appraisal would occur when the demands are appraised within the person's resources, and is characterized by positive emotion and efficient physiological activation. In a mental arithmetic task, threat appraisals predicted greater negative affect and perceived stress, whereas challenge appraisals were related to greater positive affect and task engagement (Maier et al 2003). Further, fatigue induced by cognitive overload has been shown to elevate appraisals of threat and uncontrollability (Saxby et al 2013).…”
mentioning
confidence: 96%